A fracture, a family, legal entanglement, expensive investigation, and a familiar disease - Okpechi U; Regis K; Arcia R; Soyemi K (Dove Medical Press, 2018)
Ujuchukwu Okpechi,1 Kevin Regis,2 Rosibell Arcia,1 Kenneth Soyemi1,2 1Department of Pediatrics, 2Department of Emergency Medicine, Cook County Health and Hospitals System, John H Stroger Jr Hospital, Chicago, IL, USA Abstract: Osteogenesis imperfecta can be commonly mistaken for child abuse because of similar pattern of injuries. AA is a 3-week-old baby who presented to our emergency department with excessive crying. Skeletal survey revealed subacute spiral fracture of the right humerus, right posterior eighth and ninth ribs, acute fracture of the left femur, bowing of tibia and femur, and osteopenia. Subsequent geneticist examination and genetic testing noted blue sclera and heterozygosity for a variant of COL1A gene. Keywords: fracture, legal, investigation, infant